2009
DOI: 10.1007/s12185-009-0361-y
|View full text |Cite
|
Sign up to set email alerts
|

A phase II, open-label, sequential-cohort, dose-escalation study of romiplostim in Japanese patients with chronic immune thrombocytopenic purpura

Abstract: This phase II, multicenter, open-label, sequential-cohort, dose-escalation study was designed to evaluate the safety and efficacy of romiplostim, a novel peptibody that increases platelet production, in Japanese patients with chronic immune thrombocytopenic purpura (ITP). Sequential cohorts of four patients each received romiplostim (1, 3, or 6 microg/kg) subcutaneously on days 1 and 8 of the dose-escalation phase. Patients who achieved platelet responses (doubling of baseline platelet counts to > or =50 x 10(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 22 publications
4
24
0
Order By: Relevance
“…Updated safety data are provided for over 1000 patients with a mean time on study of 76 weeks. The results reported here are similar to those observed in individual studies and in a prior pooled analysis [3,5,[7][8][9][10][11][12][13][14][15][16][17]. There was no increase in the time-adjusted rates of AEs previously designated to be of interest, including bone marrow reticulin, thrombosis, and malignancy, with longer term treatment with romiplostim (up to more than 5 years for some patients), and no new safety signals emerged.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Updated safety data are provided for over 1000 patients with a mean time on study of 76 weeks. The results reported here are similar to those observed in individual studies and in a prior pooled analysis [3,5,[7][8][9][10][11][12][13][14][15][16][17]. There was no increase in the time-adjusted rates of AEs previously designated to be of interest, including bone marrow reticulin, thrombosis, and malignancy, with longer term treatment with romiplostim (up to more than 5 years for some patients), and no new safety signals emerged.…”
Section: Discussionsupporting
confidence: 86%
“…These studies were conducted in compliance with all regulatory obligations, including institutional review board and informed consent regulations at each investigational site. The parent studies included (with ClinicalTrials.gov identifiers) phase 2 dose-finding studies (NCT00111475 part B [8] and NCT00515203 [9]), phase 3 studies (NCT00102323 [3], NCT00102336 [3], NCT00603642 [10], and NCT00415532 [11]), and singlearm studies (NCT00111475 part A [8], NCT00117143 [12], NCT00305435 [13], NCT00508820 [14], and NCT00907478 [7]). Subsequent extension/followup studies included two open-label extension studies (NCT00116688 [15] and NCT00440037 [16]) and a bone marrow follow-up study (NCT00861224 [17] from the phase 3 studies NCT00102323 and NCT00102336 [3]).…”
Section: Patients and Studiesmentioning
confidence: 99%
“…Romiplostim was previously assessed in phase 1 and 2 dose-escalation studies in Japanese patients with ITP. In these studies, romiplostim was found to be safe, well tolerated, and effective at increasing platelet counts in a dose-dependent manner [31,32]. Results were generally consistent with those from studies on non-Japanese patients.…”
Section: Introductionsupporting
confidence: 76%
“…Two second generation agents are currently licensed; one is a peptide bound to an Fc molecule, and the other is a small molecule. Both of these agents have been tested in the largest ITP trials ever performed: thus far in published clinical trial results, over 300 ITP patients have received each agent [4][5][6][7][8][9][10][11] . Currently these agents are also being/have been evaluated for other indications.…”
Section: Clinical Results With First Generation Tpo-ra Generalize Welmentioning
confidence: 99%